Childhood Tetanus Complicating Snakebite: A Case Report From a Semi-urban Area, Northwestern Nigeria - Usman, Sanni Abiola; Taslim, Lawal Olutunde; Uduak, Offiong Mayen; Lily, Musa Tawakaltu; Aliyu, Na’uzo Mamman (Cerrahpaşa Medical Journal, 2023)
For more than 6 decades, snakebite has been recognized as an important global public health problem. Such bites can be complicated by mortality and various forms of morbidities including tetanus. Tetanus as a complication of snakebite is rare, more so among children. We present a case of a 13-year-old adolescent male rural dweller with lockjaw and spasms a week following snakebite. He had no immunization in infancy and was not administered tetanus toxoid after the incidence. Important findings at presentation were healed ulcer on the left big toe, board-like rigidity of the ante- rior abdominal wall, and spasms. He was managed for tetanus complicating snakebite and discharged home after a total of 26 days of hospitalization. The case demonstrates the need to strengthen immunization coverage in rural communities while improving health-seeking behaviors through health education. Victims of snakebites should be encouraged to seek orthodox care and be administered intramuscular tetanus toxoid. Cite this article as: Usman SA, Taslim LO, Uduak OM, Lily MT, Aliyu NM. Childhood tetanus complicating snakebite: A case report from a semi-urban area, Northwestern Nigeria. Cerrahpaşa Med J. 2023;47(2):239-240.